2000
DOI: 10.1073/pnas.97.26.14156
|View full text |Cite
|
Sign up to set email alerts
|

A model of fibrin formation based on crystal structures of fibrinogen and fibrin fragments complexed with synthetic peptides

Abstract: A blood clot is a meshwork of fibrin fibers built up by the systematic assembly of fibrinogen molecules proteolyzed by thrombin. Here, we describe a model of how the assembly process occurs. Five kinds of interaction are explicitly defined, including two different knob-hole interactions, an end-to-end association between ␥-chains, a lateral association between ␥-chains, and a hypothetical lateral interaction between ␤-chains. The last two of these interactions are responsible for protofibril association and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
222
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(242 citation statements)
references
References 49 publications
(50 reference statements)
17
222
0
2
Order By: Relevance
“…The precise mechanisms responsible for the lateral aggregation of protofibrils remain largely unknown [3]. The following portions of the fibrinogen structure have been shown to contribute to lateral aggregation: knobs 'B' [7], holes 'b' [7], γC modules [7], βC modules [7], αC regions [26], coiled coils [27], and carbohydrates at residues Bβ364Asn and γ52Asn [28]. γ350-360 and γ370-380 residues in the γC module are critical for lateral aggregation, and the deletion of γN319 and γD320 (Otsu I) fibrinogen induced disruptive conformational changes in these region, resulting in larger decreases in lateral aggregation than the substitution of γD320 (Okayama II) fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise mechanisms responsible for the lateral aggregation of protofibrils remain largely unknown [3]. The following portions of the fibrinogen structure have been shown to contribute to lateral aggregation: knobs 'B' [7], holes 'b' [7], γC modules [7], βC modules [7], αC regions [26], coiled coils [27], and carbohydrates at residues Bβ364Asn and γ52Asn [28]. γ350-360 and γ370-380 residues in the γC module are critical for lateral aggregation, and the deletion of γN319 and γD320 (Otsu I) fibrinogen induced disruptive conformational changes in these region, resulting in larger decreases in lateral aggregation than the substitution of γD320 (Okayama II) fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…e l s e v i e r . c o m / l o c a t e / t h r o m r e s fibrin polymerization and the interaction site for platelet thrombus formation have been defined in the γC module; hole 'a' (Q329, D330, and D364) [4,5], high affinity calcium-binding site (D318, D320, F322, and G324) [6], D:D interaction site (γ275-300) [5], lateral aggregation sites (γ350-360 and γ370-380) [7], FXIIIa-catalyzed cross-linking site (E398 on one molecule and K406 on another molecule) [8], and platelet-binding site (the last four residues, γ408-411) [9]. Almost 300 species of genetic mutations in the fibrinogen genes, FGA, FGB, and FGG, have been associated with either the phenotype of afibrinogenemia, hypofibrinogenemia, dysfibrinogenemia, or renal amyloidosis, as listed in the fibrinogen variant data base [10], and the function and genetic and/or post-translational changes causing these phenotypes have been analyzed by molecular bases.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The end-to-end alignment of monomers in each protofibril strand requires so-called D:D interaction, which abuts the -chain of two adjacent molecules [5]. In the second step, these protofibrils grow in length and thrombin cleaves FpB, which exposes a new N-terminal segment, knob 'B', which likely interacts with hole 'b' in the  module of the D region of another molecule to promote lateral aggregation of the protofibrils [6], resulting in the formation of thicker fibers and finally an insoluble fibrin clot consisting of a multi-stranded and branched fiber network [7].…”
Section: Introductionmentioning
confidence: 99%
“…Protofibrils are expected to take a hexagonal close packing formation as cylinders within the fiber bundle [44]. The protofibril volume fraction (protofibril volume/fiber volume) would then be:…”
Section: Turbidimetrymentioning
confidence: 99%
“…Moreover, although it has been shown that void spaces in-between protofibrils within the fibrin fibers can serve as "nanocavities" that could entrap therapeutic agents [43], there has not been a quantitative assessment of the effect of intrafibrillar structure on the diffusion of solutes. Whether or not solutes can diffuse through individual fibers has remained an open question since it was stated in a seminal paper on fibrin formation [44], even though intrafibrillar diffusion has been demonstrated and measured for collagen [45].…”
Section: Introductionmentioning
confidence: 99%